Proliferative effects of urogastrone-EGF on the intestinal epithelium. (1987) - Goodlad, R A; Wilson, T J; Lenton, W; Gregory, H; McCullagh, K G; Wright, N A
Abstract : The effects of B-urogastrone/human epidermal growth factor on intestinal epithelial cell proliferation were studied in rats in which intestinal cell proliferation was reduced to a steady state basal level (by maintaining the rats on total parenteral nutrition). Increasing doses of urogastrone progressively raised the two hour collection of metaphases and intestinal weights. The crypt cell production rate was measured in animals maintained parenterally with or without urogastrone, and in rats fed a standard laboratory ration. Continuous infusion of 15 micrograms per rat per day of recombinant beta urogastrone (a dose which has a minimal effect on gastric acid secretion) significantly increased cell proliferation and intestinal tissue weights throughout the gastrointestinal tract. Intravenous infusion of urogastrone was also effective in restoring cell proliferation when it was infused after the intestine had become hypoproliferative. Urogastrone administered through an intragastric cannula thrice daily had no significant effect on either intestinal weight, crypt cell production rate, or metaphase collection.